2018
DOI: 10.1016/j.wneu.2017.12.077
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Cerebrovascular Abnormalities Detected in Various Diagnostic Subgroups of Spontaneous Subarachnoid Hemorrhage in the Modern Era

Abstract: Frequency of vascular abnormalities in spontaneous SAH is lower than the traditionally quoted figure, which has diagnostic and prognostic implications for patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Moreover, it should be noted that there was one case of unruptured aneurysm revealed in patients with negative head CT that suggests that detailed vascular imaging may lead to significant findings. This finding stays in line with results of Chong et al, who discovered presence of vascular abnormalities in over 40% of subjects with CT-negative SAH [15].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, it should be noted that there was one case of unruptured aneurysm revealed in patients with negative head CT that suggests that detailed vascular imaging may lead to significant findings. This finding stays in line with results of Chong et al, who discovered presence of vascular abnormalities in over 40% of subjects with CT-negative SAH [15].…”
Section: Discussionsupporting
confidence: 93%
“…They found that probable overlooking of SAH did not influence negatively their prognosis [16]. Chong et al reported similar observation as only 1.3% of patients with CT-negative SAH experienced further re-bleeding [15].…”
Section: Discussionmentioning
confidence: 84%